TEM STUDY OF PROGRESSIVE ALTERATION OF IGNEOUS BIOTITE TO KAOLINITE THROUGHOUT A WEATHERED SOIL PROFILE - Dong H.; Peacor D.R.; Murphy S.F. (My University, 1998)
TEM characterization of progressive alteration of igneous biotite to kaolinite throughout a weathered soil profile was carried out to study the mechanisms of the reaction from biotite to kaolinite. A biotite-like phase with d(001) # 10.5 #9 but with a higher Al/Si ratio and lower Fe, Mg, and K contents forms as a first, intermediate alteration product of igneous biotite. This phase is referred to as altered biotite. Two different alteration mechanisms are responsible for the altered biotite-kaolinite reaction: (1) reaction of one layer of altered biotite to form two layers of kaolinite and (2) transition of one layer of altered biotite to one layer of halloysite, which subsequently reacted to form one layer of kaolinite. Metastable intermediate altered biotite and halloysite form at low temperatures, where reactions are sluggish, as consistent with the Ostwald step rule, and in direct contrast to equivalent reactions at high temperatures.